2004
DOI: 10.1124/jpet.104.073817
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Group III Metabotropic Glutamate Receptors in Control of Nociception and Dorsal Horn Neurons in Normal and Nerve-Injured Rats

Abstract: Increased glutamatergic input to spinal dorsal horn neurons constitutes an important mechanism for neuropathic pain. However, the role of group III metabotropic glutamate receptors (mGluRs) in regulation of nociception and dorsal horn neurons in normal and neuropathic pain conditions is not fully known. In this study, we determined the effect of the group III mGluR specific agonist L(ϩ)-2-amino-4-phosphonobutyric acid (L-AP4) on nociception and dorsal horn projection neurons in normal rats and a rat model of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 37 publications
5
60
0
Order By: Relevance
“…Indeed, intra-DS administration of (S)-3,4-DCPG did not change thermal nociception, MWT, and the ongoing and tail flick-evoked ON and OFF cell activity in sham-operated animals. Evidence that group III mGluR stimulation inhibits pain in different pathological pain states of various etiologies but not in normal conditions has been already reported (Chen and Pan 2005;Goudet et al 2008;Neugebauer 2006;Palazzo et al 2008Palazzo et al , 2011Palazzo et al , 2013Zhang et al 2009). In particular, we have found that intra-CeA (S)-3,4-DCPG failed to change pain and affective behavior, neurotransmitter release, and RVM cell activity in physiological conditions (Palazzo et al 2008.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, intra-DS administration of (S)-3,4-DCPG did not change thermal nociception, MWT, and the ongoing and tail flick-evoked ON and OFF cell activity in sham-operated animals. Evidence that group III mGluR stimulation inhibits pain in different pathological pain states of various etiologies but not in normal conditions has been already reported (Chen and Pan 2005;Goudet et al 2008;Neugebauer 2006;Palazzo et al 2008Palazzo et al , 2011Palazzo et al , 2013Zhang et al 2009). In particular, we have found that intra-CeA (S)-3,4-DCPG failed to change pain and affective behavior, neurotransmitter release, and RVM cell activity in physiological conditions (Palazzo et al 2008.…”
Section: Discussionmentioning
confidence: 96%
“…Activation of group II and III mGluRs also inhibits glutamatergic transmission in many brain regions and in the normal spinal cord (Jane et al, 1996;Conn and Pin, 1997;Gerber et al, 2000). Activation of group II and III mGluRs attenuates the firing activity of spinal dorsal horn neurons in acute and chronic pain models (Neugebauer et al, 2000;Chen and Pan, 2005). Some group II and III mGluRs are also localized on the GABAergic interneurons and terminals in the spinal cord (Jia et al, 1999), and group II and III mGluR agonists decrease synaptic GABA release in normal spinal cord slices (Gerber et al, 2000).…”
Section: Effect Of Group II and Iii Metabotropic Glutamate Receptor Amentioning
confidence: 99%
“…Intrathecally administered group II and III mGluR agonists inhibit the responses of sensitized spinothalamic tract cells, mechanical hypersensitivity and allodynia induced by nerve injury, interleukin-1β, capsaicin and carrageenan (Neugebauer et al, 2000;Dolan & Nolan, 2002: Fisher et al, 2002Chen & Pan, 2005;Soliman et al, 2005;Jung et al, 2006). These experimental findings in the behavioral and electrophysiological studies indicate that group I, II and III mGluRs in the spinal cord may contribute to the nociceptive responses with a variety of other causes as well as inflammation and nerve injury.…”
Section: Discussionmentioning
confidence: 92%
“…administration of group I mGluR antagonists (Neugebauer et al, 1994;Bhave et al, 2001;Zhou et al, 2001;Hudson et al, 2002). Group II and III mGluR agonists inhibit peripheral inflammationand nerve injury-induced hyperalgesia as well as responses of spinothalamic tract cells to noxious mechanical stimulation and capsaicin (Dolan & Nolan, 2002;Fisher et al, 2002;Chen & Pan, 2005;Soliman et al, 2005). (2S, 1'R, 2'R, 3'R)-2-(2',3'-dicarboxycyclopropyl)glycine (group II mGluR agonist) and (S)-2-amino-4-phosphonobutanoate (group III mGluR agonist) depress excitatory postsynaptic potential (EPSP) evoked by the stimulation of primary afferent fibers in the spinal cord dorsal horn .…”
Section: Introductionmentioning
confidence: 99%